Effect of Customer Relationship Management on Repeat Patronage in Ado-Ekiti Retail Organizations (UNIZIK Journal of Marketing, 2024)
The study focused on the relationship between customer relationship management and repeat patronage in Ado-Ekiti retail organizations. Specifically, the study examined the relationship between customer service, complain handling management, customer intimacy and repeat patronage. The study used survey research design. Data was gathered from primary source.  The target populations for the study comprise of customers of selected retail organization (supermarkets and food stores) in Ado-Ekiti under study. purposive sampling techniques was used to draw a sample of 180 from the respondents. Questions structured on a 5-point Likert scale were used in the survey to obtain responses from participants. Data from 180 respondents were analyzed using Pearson product moment correlation to examine the relationship between customer service, complaint handling, customer intimacy and repeat patronage. The findings based on the statistical tool utilised in the study revealed that there was strong significant relationship between customer service, complain handling management, customer intimacy and repeat patronage. The study conclusion relied on the findings. The study attracts the following recommendations: The management of retail outlet in Ado- Ekiti should improve their strategies to boost customer service, they should develop a measure to handle complain effectively in order to encourage repeat patronage of consumer goods and they should imbibe the strategy to create customer intimacy to entice numerous customers to repeat patronage
Keywords: Customer relationship management; Repeat patronage; Customer service; Customer intimacy